Performance characteristics of a photovoltaic panel integrated with PCM packed cylindrical tubes for cooling - Nitin Agarwal; Abhishek Saxena (International Journal of Sustainable Energy, 2022)
The effect of an increasing volume of the phase change material (PCM) and large heat transfer area have been assessed for controlling the higher surface temperature of the photovoltaic (PV) module which influences conversion efficiency and power output. For this, a bed of multi-cylindrical copper tubes filled with PCM has been prepared. The performance evaluation has been done on three different configurations such as module ‘B’ integrated with 91 tubes in the first configuration, module ‘C’ integrated with 181 in the second configuration and module ‘D’ integrated with 271 in the third configuration. The results obtained from three configurations are compared with the reference module (module A). All the tested panels are found to be better than the reference panel, but panel D is found to be the best configured among all tested panels, which showed the average per cent reduction of around 20.76% in the cell temperature and average per cent increment in 6.49% in conversion efficiency and 6.67% in power output.